Analisa Penerimaan Tekhnologi Artificial Intelligence Generative Dengan Menggunakan Metode UTAUT 2 - Ibnu Alfarobi; Sofian Wira Hadi; Amin Nur Rais; W Warjiyono; Wawan Kurniawan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The rapid development of information and communication technology has changed various aspects of human life and the impact of current technological developments is that there are many new technologies and of course new technology can provide benefits for users and developers. AI has had an impact on aspects of economics, politics, science and education in the current era. One of the most popular forms of AI is ChatGPT. The success of a new technology will of course be assessed and felt by users who will later be assessed whether the new technology will help and meet their needs. Several previous studies tested AI using Google Trends, Analysis of Trends in Indonesian People's Interest in Artificial Intelligence in Welcoming Society 5.0: Study using Google Trends. Analyzing the acceptance of Generative AI technology using the UTAUT 2 model is the main objective of this research. Factors that have a very positive and significant influence are the habit factors on behavior intention and habit on use behavior